Internet of things sensors network for outdoor environmental quality monitoring (IOT-OQEM) - Chua, Wen Kai (Nanyang Technological University, 2022)
Weather stations or Environmental Monitoring Stations currently used to collect information on Outdoor Environmental Quality (OEQ) are rigid, bulky, and expensive to implement. The Outdoor Environmental Quality Monitoring Systems (OEQMS) plays a crucial role to provide data to the enforcement agencies in maintaining healthy outdoor air quality but there is urgent need to extend the area of coverage for outdoor environmental monitoring. In recent years, the advancement of Internet of Things (IoT) and compact sensor technology have enabled the development of environmental monitoring systems at low cost with adequate accuracy and precision. This allows the deployment of large quantity of such low-cost standalone monitoring systems over vast areas for long term environmental monitoring without human intervention. Many of those standalone monitoring systems are often powered on batteries and limited by battery capacity. Environmental energy harvesting such as using solar panels and capability of putting the energy consuming IoT-sensors modules in extensive deep sleeping mode to conserve energy could be used to prolong operation uptime. The aim of this project was to develop the IoT-sensor modules using Argon IoT microcontroller from Particle Industries Inc. to interface with compact environment sensors to capture parameters that include temperature, humidity, CO2 concentration and PM2.5 levels before wirelessly communicating the measurements through the IoT-sensor network. The emphasis on the selection of commercially available compact sensors for integration with the Argon IoT microcontroller in this project was the simple I2C data communication between Argon and the sensors. The project developed and conceptualized an IoT-sensor network architecture to enable wireless data transmission through a combination of Bluetooth Low Energy (BLE) and WIFI protocols. External antennas were incorporated into the system design to extend the transmission range. Lastly, an integrated outdoor sensor enclosure was developed to house all IoT- sensor modules and supporting electrical components for deployment in the outdoor environment. In conclusion, six different sensors that captured nine different parameters are integrated with the IoT microcontroller and the feasibility of wireless communication over BLE and WIFI was demonstrated in an IoT-sensor network. A prototype helical enclosure that featured a modular design was 3D printed using Multi Jet Fusion (MJF) technology.